Optimization of dimple configurations on heat dissipation of aluminium flat surface - Ganesan, Hema Nanthini (2018)
In the car manufacturing industry,countless inventions, improvements, and modifications are continuously being updated to meet customer expectations. Therefore, engineers and inventors always give higher priority to improving every part of a vehicle. However, there are still numerous reports of customer frustration, especially in medium-priced cars parts reliability. One of the main issues are involves engine mounts, which are exposed to high temperatures from the engine heat,leading to a short life span. An engine mount is the part that holds the engine to the body or to the engine cradle (sub-frame) of the car. The engine mount exposed high heat energy from the engine during the combustion process (130°C). This causes the engine mount to lose its mechanical strength, resulting in a short service life. The lifespan of the engine mount depends on the effectiveness of heat dissipation during dynamic state. Therefore, it is essential to improve the heat transfer of the engine mounting. Thus, the aim of this research is to develop and evaluate a spherical dimple profile for a smooth surface to enhance heat transfer rate. It is widely known that introducing a dimple profile results in improved heat transfer over a surface. This research focuses on geometric modification and optimization of cooling paran1eters for a spherical dimpled surface of an aluminium block. The aluminium block is used throughout this experiment because it is one of the best conductors of heat. Thus, in this experiment, the dimpled design is the main focus.In this project, experimental and numerical investigation were carried out to examine the cooling effect and flow structure of the spherical dimple profile during steady laminar flow in a wind tunnel. Seventeen different sets of parameters related to the dimple diameter ( 10-14 mm),dimple orientation ( 60°-90° angle),and airflow velocity (16-18 m/s) were studied. The Box-Behnken of Response Surface Methodology (RSM) was used as a Design of Experiments (DoE) tool to evaluate the effect of these parameters on cooling time. This work applies Analysis of Variance (ANOV A) in order to establish the significant effect of the input parameters.ANSYS Fluent software was used as a simulation tool to analyze the flow structure of the dimpled surface. The optimal cooling time is produced from the experiment is 7.23 minutes with a relative error of 5.24% compared to the prediction results.The optimal parameters are a dimple diameter of 12 mm,a dimple orientation angle of 60°,and an airflow velocity of 18 m/s.